Beyond health, beyond choice : breastfeeding constraints and realities - Smith, Paige Hall; Hausman, Bernice L.; Labbok, Miriam H. (Critical issues in health and medicine., 2012)
Beyond Health, Beyond Choice is a multidisciplinary collection of essays written by thirty-seven contributors that examines the role of feminist theory in the promotion of breastfeeding by public health authorities. Essays are arranged thematically and consider breastfeeding in relation to health care; work and family; embodiment (specifically breastfeeding in public); economic and ethnic factors; guilt; violence; and commercialization.